2021
DOI: 10.1142/s2010135x21500065
|View full text |Cite
|
Sign up to set email alerts
|

Critical temperature below the Curie temperature of ferroelectric ceramics PZT

Abstract: The article presents the results of research the pre-transitional features of the behavior of solid solutions based on lead zirconate-titanate. The presence of a “special” critical temperature [Formula: see text] on the temperature dependences of the permittivity [Formula: see text] and the remanent polarization [Formula: see text], preceding the temperature of the paraelectric phase transition at the Curie temperature [Formula: see text], is noted. In the temperature range [Formula: see text], the [Formula: s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Nonetheless, the reversability of the ferroelectric properties and the relatively low temperature at which the anomalous Al 0.72 Sc 0.28 N lattice expansion would be activated with respect to the study of Wolff et al could also suggest that defects affect the electrical properties even in the early stage of their activation without implying any irreversible structural change in the ferroelectric film and that the hysteresis behavior could be due to defect redistribution. The existence of a temperature region in which ferroelectric properties are completely reversible was already observed in other ferroelectrics, such as PZT and Hf 1– x Zr x O 2 . , Remarkably, it is demonstrated that Al 0.72 Sc 0.28 N has this property over a 375 K temperature range.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…Nonetheless, the reversability of the ferroelectric properties and the relatively low temperature at which the anomalous Al 0.72 Sc 0.28 N lattice expansion would be activated with respect to the study of Wolff et al could also suggest that defects affect the electrical properties even in the early stage of their activation without implying any irreversible structural change in the ferroelectric film and that the hysteresis behavior could be due to defect redistribution. The existence of a temperature region in which ferroelectric properties are completely reversible was already observed in other ferroelectrics, such as PZT and Hf 1– x Zr x O 2 . , Remarkably, it is demonstrated that Al 0.72 Sc 0.28 N has this property over a 375 K temperature range.…”
Section: Resultsmentioning
confidence: 54%
“…Ferroelectric materials with particularly high Curie temperature are thus required to satisfy the temperature requirements for harsh environments and space applications. Lead zirconium titanate (PZT) has a Curie temperature lower than 673 K. , Moreover, the initial interest in PZT encountered the challenges of integration into complementary metal-oxide semiconductor (CMOS) technology due to lead inclusion, high crystallization temperatures, and weakly bound oxygen; thus, the most advanced PZT ferroelectric random-access memory (FeRAM) technology has stalled at the 130 nm node . Among the other perovskite ferroelectrics, bismuth ferrite (BiFeO 3 ) has the largest Curie temperature (1103 K), but the high leakage, poor switching speed, and low cycling endurance compared to other ferroelectrics, as well as the presence of iron, are still important limiting factors for its adoption in memory-related applications .…”
Section: Introductionmentioning
confidence: 99%
“…It is found that the temperature of maximum εr for each frequency has no apparent changes with frequency, indicating that they are normal ferroelectric rather than relaxor ferroelectric ceramics. The temperature of maximum εr for this kind of ceramics is Curie temperature [16] . It is observed that TC vary from 310 ℃ to 320 ℃, indicating that the operating temperature range of ceramics will be wider.…”
Section: Resultsmentioning
confidence: 99%
“…The characterization of material properties is the first and critical step in the design of devices because the piezoelectric dielectric properties of materials will directly affect the final performance of the device, which is why scholars have studied it extensively over the past years ( Kuzenko, 2021 ; Yang L. et al, 2021 ). Several kinds of literature have pointed out that the energy transmission efficiency is higher when the ultrasonic stimulation frequency is lower than 1 MHz ( Hayner and Hynynen, 2001 ; White et al, 2006 ), so it is suitable to study the acoustic characteristics of ultrasonic transducers with different structures at 400 kHz.…”
Section: Methods and Resultsmentioning
confidence: 99%